Understanding the adoption of Halal Logistics through critical success factors and stakeholder objectives - Abid Haleem; Mohd Imran Khan; Shahbaz Khan (Logistics, 2021)
Catering to Halal in the industry requires the explicit adoption of Halal Logistics (HL) to avoid the risk of cross-contamination and ensure that Halal products are safe, hygienic, nutritious, pure, unadulterated, and consistent with their labelling. We identify the need for meaningful research constructs relating to the appropriate adoption of Halal logistics through an extensive literature review. This paper identifies Critical Success Factors (CSF) and develops corresponding constructs that are fundamental for understanding the adoption of Halal logistics. This research also identifies the stakeholders involved and their objectives to facilitate the system design. As a starting point, from the existing literature, we adopt a structural model of CSFs to implement Halal Logistics. After that, this paper identifies and validates these CSFs with the support of extensive literature-based reviews, senior managers of Halal exporting organisations, Halal accrediting bodies, and professionals working in logistics and the cold chain. The research findings indicate that logistics service providers need to successfully upgrade their facilities to adopt Halal practices in their operations. Moreover, the role of governments is to reduce bureaucratic complexity so as to improve the ease with which businesses can implement HL. It becomes clear, from the analysis, that logistics service providers have the most prominent role in the effective adoption of the Halal supply chain. Consumers have a more prominent role than government support in the growing market of Halal products. This paper contributes to the identification of stakeholders' objectives, which will facilitate the efficient adoption of Halal logistics and provide a direction for undertaking associated future work.
Keywords: 650; Halal; Halal Logistics (HL); logistics; research constructs; Toiyyib; stockholder's objectives